Patterns and Prevalence of Dyslipidemia in Diabetics Presenting with STEMI VS Non-STEMI in Local Population of Sialkot, Pakistan (Medical Forum Monthly, 2021)
Objective: The prospect of this study is to ascertain the safe ranges of TGs in diabetics to prevent the mortality and morbidity associated with transmural infarcts (STEMI).Study Design: Observational study. Place and Duration of Study: This study was conducted at the Cardiology Department of Allama Iqbal Memorial Teaching Hospital, Sialkot during Nov 2019-Nov 2020.Materials and Methods: A total of 1000 patients having age ranges 20-80 years were inducted during Nov 2019-Nov 2020 presenting in ER with chief complaint of typical chest pain having concomitant diabetes. HbA1c performed with Rosche Cobbas C311.Results: The data was collected from 1000 patients. The mean age of the patients was 51.3 ± 11.5 years in STEMI patients and 57.4 ± 9.4 in NSTEMI. 45 (45%) have diabetic history with STEMI and 55 (55%) with NSTEMI patients. 81 (81%) have smoking history and 17 (17%) have family history of CVD with STEMI. Our study revealed that patients with poor control of their glycemic indexes, HbA1c >7 had deranged cholesterol profile especially triglycerides were significantly raised beyond >150mg/dl.Conclusion: The intricate balance of natural antithrombins and atherogenic factors is hence disturbed in context of the people having diabetes and hypertriglyceridemia together, paving the way for the most fatal variants of Acute Coronary Syndrome (STEMI>NSTEMI).